Peran Guru Sebagai Agen Pembaharu dalam Meningkatkan Kualitas Pembelajaran yang Inovatif di Sekolah Dasar - An Nisaa'an Najm Al Inu; Desnita Fitriani; Elza Amalia Salsya Bani; Moch Lucky Winandar (Departement of Mathematics Education, 2023)
This article aims to provide information regarding the important role of the teacher in terms of improving the quality of learning with more innovative creative ideas, especially at the elementary school level. Innovative learning that is created must be in accordance with the learning objectives that have been determined by the teacher, be able to achieve what has been planned, have varied abilities in implementing learning and learning strategies that are tailored to the interests of learning and the needs of students, and be able to improve the quality of the learning process and results. learning aimed at improving the quality of education as a whole. This research method uses descriptive qualitative methods based on literature studies or literature reviews such as scientific journals, electronic books and other sources whose accuracy has been confirmed with the aim of providing some information and solutions in identifying the problems discussed in this research.